Komunikasi Organisasi Pada Pemerintahan Desa Karang Raharja Kecamatan Cikarang Utara Kabupaten Bekasi dalam Menunjang Pelayanan Administrasi Kepada Masyarakat - Azzahra, Nadia Fatimah; Putri, Yuliani Rachma (eProceedings of Management, 2023)
In implementing the organizational communication flow, coordination is needed which is built between employees, this also has an impact on the quality of services provided in the government sector. This creates an opportunity as well as an opportunity to improve the flow of organizational communication and provide services to the public. The Karang Raharja Village Government has implemented organizational communication channels both vertically upwards and downwards, horizontally and diagonally, then by implementing these communication channels it can support administrative services to the community. The research method used is a qualitative method with a constructivism paradigm and data collection using interview and observation techniques. The results of this study indicate that organizational communication channels have been effectively implemented, but several factors are still the cause of the ineffectiveness of providing services to the community, one of which is the delay in service delivery.Keywords-Organizational CommunicationCommunication flow, Service Effectiveness, Karang Raharja Village